Newer Developments in the Synthesis of P-Heterocycles (Current Organic Chemistry, 2019)
Due to an overlook the reference nos. 1, 6, 8, 15, 16, 34, 40, 41, 46, 47, 48, 68, 74, 80, 81 & 96 were published erroneously in the article, entitled: “Newer Developments in the Synthesis of P-Heterocycles” in “Current Organic Chemistry”, 2019, Vol. 23, No. 12, pp. 1342- 1355.”